Pemberdayaan Di Panti Asuhan Bahagia Melalui Pelatihan Kerajinan Hiasan Manik Untuk Menumbuhkan Jiwa Kewirausahaan - Jasri, Jasri; Fitriani, Fitriani; Muliani, Rizka; Sulviani, Sulviani; Salsabila, Windiyarti; Antea, Riris Ode; Syahdewa, Adjie Arya; Alam, Syamsu; Siskayanti, Siskayanti; Aulia, Andini; Rinayanti, Rinayanti (Universitas Negeri Gorontalo, 2025)
Bead craft training at the Bahagia Orphanage aims to foster an entrepreneurial spirit and improve the skills of foster children. This activity is carried out through empowerment and mentoring methods, with stages of distributing tools and materials, presenting video tutorials, and direct practice in making products such as bracelets, rings, and key chains. During the training, participants received intensive guidance from facilitators so that they were able to develop their creativity and courage to innovate. The evaluation results showed a significant increase in the technical skills and entrepreneurial motivation of children. In addition, the interactive learning atmosphere and the use of visual media have proven effective in accelerating understanding of the material. This program also has a positive impact on the formation of independent and creative characters, as well as opening up opportunities for the development of small craft-based businesses in the orphanage environment. Thus, this training is expected to be a sustainable empowerment model in building a productive and adaptive young generation to future economic challenges.